NEW BIOMOLECULAR TARGETS FOR ANTIEPILEPTIC DRUGS - T. A. Voronina; G. G. Avakyan; L. N. Nerobkova; S. A. Litvinova; G. N. Avakyan (Эпилепсия и пароксизмальные состояния, 2016)
The review presents data on new antiepileptic drugs (AEDs), which have been applied in medical practice in recent years. New AEDs have different spectrum of pharmacological effects and mechanism of action. The authors presented the classification of AEDs for their ability to influence the processes of excitation and inhibition in the central nervous system. This article contains information about AEDs, blocking or modifying the ionic conductivity of the voltagedependent Na+ and Ca++-channels; AEDs, blocking glutamate receptors; AEDs, activating the ionic conductivity of K+ channels; AEDs, enhancing the braking effect of GABA